2005
DOI: 10.1103/physrevlett.94.147602
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Formation of Polar Nanoregions inPb(Mg1/3Nb2/3)O3<

Abstract: Using neutron pair distribution function analysis over the temperature range from 1000 to 15 K, we demonstrate the existence of local polarization and the formation of medium-range, polar nanoregions (PNRs) with local rhombohedral order in a prototypical relaxor ferroelectric Pb(Mg(1/3)Nb(2/3))O3. We estimate the volume fraction of the PNRs as a function of temperature and show that this fraction steadily increases from 0% to a maximum of approximately 30% as the temperature decreases from 650 to 15 K. Below T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
149
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(172 citation statements)
references
References 34 publications
21
149
1
1
Order By: Relevance
“…These intriguing materials exhibit unusual features, such as a frequency-dependent and broad dielectric response versus temperature while remaining macroscopically paraelectric down to 0 K [28]. They also display several characteristic temperatures (i.e., the T b Burns temperature, the T * temperature and the T m temperature) that are associated with a subtle change in some physical properties [29][30][31][32][33][34]. For instance, in Ba(Zr 0.5 Ti 0.5 )O 3 (BZT) relaxor ferroelectrics, simulations [35] indicate that the Burns temperature (below which the dielectric response does not obey the Curie-Weiss law [36]) is T b ≃ 450 K , T * ≃ 240 K, and T m ≃ 130 K is the temperature at which the dielectric response exhibits a peak, as also in-line with measurements in BZT compounds [33,34,37,38].…”
Section: ∂T ∂E Smentioning
confidence: 99%
“…These intriguing materials exhibit unusual features, such as a frequency-dependent and broad dielectric response versus temperature while remaining macroscopically paraelectric down to 0 K [28]. They also display several characteristic temperatures (i.e., the T b Burns temperature, the T * temperature and the T m temperature) that are associated with a subtle change in some physical properties [29][30][31][32][33][34]. For instance, in Ba(Zr 0.5 Ti 0.5 )O 3 (BZT) relaxor ferroelectrics, simulations [35] indicate that the Burns temperature (below which the dielectric response does not obey the Curie-Weiss law [36]) is T b ≃ 450 K , T * ≃ 240 K, and T m ≃ 130 K is the temperature at which the dielectric response exhibits a peak, as also in-line with measurements in BZT compounds [33,34,37,38].…”
Section: ∂T ∂E Smentioning
confidence: 99%
“…Measurements using neutron pair distribution function analysis have confirmed that at low temperatures no long-range polar order is present with a maximum of ϳ1 / 3 of the sample having polar order. 6 Under the application of a strong electric field, a sharp and frequency-independent peak in the dielectric response is observed to remain after the removal of the electric field at low temperatures indicative of a well defined structural distortion. 7 However, NMR measurements have shown that it is difficult to associate this with the presence of a longranged ferroelectric ground state as two components are measured in the NMR line shape and at least half of the crystal remains in a disordered state.…”
Section: Introductionmentioning
confidence: 99%
“…39 In this case, a strong dynamical behavior of the dielectric constant would be expected, and given the mismatch between the local and the long-range orders found in EuTiO 3 , the system could act as a relaxor ferroelectric. 40 In these systems, the disorder is typically introduced extrinsically through chemical doping, while in EuTiO 3 the structure itself seems to be willing to organize at a nanoscopic scale (forming domains of the order of ∼20Å).…”
Section: Pdf Analysismentioning
confidence: 99%